2022
DOI: 10.1021/acsanm.2c03074
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ion Beam vs Focused Electron Beam Deposition of Cobalt Silicide Nanostructures Using Single-Source Precursors: Implications for Nanoelectronic Gates, Interconnects, and Spintronics

Abstract: Direct-write techniques for the fabrication of nanostructures are of specific interest due to their ability for a maskless fabrication of any arbitrary three-dimensional shape. To date, there is a very limited number of reports describing differences in the focused ion and electron beam induced deposition (FIBID/FEBID) for the same precursor species. This report contributes to filling this gap by testing two single-source precursors for the deposition of cobalt silicide in Ga-ion beam writing and reveals H 2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Moreover, similar surface science studies have demonstrated that ion bombardment of condensed precursor layers results in films with a much higher metal content, when compared to pure electron irradiation. , In addition, the studies do not describe a preferential sputtering of either metal in bimetallic CpFe­(CO) 2 Re­(CO) 5 by Ar + ion bombardment of condensed precursor films but rather C 5 FeRu layer formation with carbonyls being liberated efficiently . This is in line with FIBID of a 2:1 Co:Si metal/metalloid ratio from H 2 Si­(Co­(CO) 4 ) 2 . In contrast, H 3 SiCo­(CO) 4 -derived FIBID material revealed significant Si loss, while FEBID material retained the metal/metalloid ratio, which was attributed to increasing impact of sputtering effects in FIBID due to low growth rates. , …”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Moreover, similar surface science studies have demonstrated that ion bombardment of condensed precursor layers results in films with a much higher metal content, when compared to pure electron irradiation. , In addition, the studies do not describe a preferential sputtering of either metal in bimetallic CpFe­(CO) 2 Re­(CO) 5 by Ar + ion bombardment of condensed precursor films but rather C 5 FeRu layer formation with carbonyls being liberated efficiently . This is in line with FIBID of a 2:1 Co:Si metal/metalloid ratio from H 2 Si­(Co­(CO) 4 ) 2 . In contrast, H 3 SiCo­(CO) 4 -derived FIBID material revealed significant Si loss, while FEBID material retained the metal/metalloid ratio, which was attributed to increasing impact of sputtering effects in FIBID due to low growth rates. , …”
Section: Introductionsupporting
confidence: 62%
“…It should be noted that the lowest resistivity values for other FIBID deposits derived by Ga + ions based on Pt (∼800 μΩ·cm), Pd (∼1000 μΩ·cm), Co 2 Si (∼330 μΩ·cm), and W (∼200 μΩ·cm) , typically are fairly high when compared to those of pure metals. Exceptions are the higher-purity Cu (∼50 μΩ·cm) and Co-based (∼20 μΩ·cm) FIBID material, but significant differences have been observed depending on compositional changes and postgrowth processing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Focused Electron Beam-Induced Deposition (FEBID) method [1][2][3][4] is increasingly employed to deposit various layers and 3D structures at the nanoscale. [5][6][7][8][9] In FEBID, a high-energy electron beam is used to induce the decomposition of precursor gases, leading to the deposition of the metal component from the precursor onto the surface. 1,2,4 Various types of precursors have been utilized in FEBID, including W(CO) 6 , Et 4 Pb, Fe(CO) 5 , Fe 2 (CO) 9 , Co 2 (CO) 8 , HCo 3 Fe(CO) 12 , AgO 2 Me 2 Bu and many others.…”
Section: Introductionmentioning
confidence: 99%